Hygiene condition of water use and sanitation facilities at urban slums: analysis of port city Chittagong, Bangladesh = Wyposażenie sanitarne w slamsach miejskich - analiza na podstawie miasta portowego Chittagong, Bangladesh - Muhit, I.B.; Chowdhury, S. Tasneem; Nahid, Nurangir; Zaman, M.F. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Low income community development is the prerequisite for the overall development of a society. There are different kinds of parameters to widen community development, such as health, economic, social, a living pattern, etc. Sanitation condition is the crucial aspect that is directly or indirectly inter bond with all the parameters.
Keywords: warunki sanitarne; higiena; zaopatrzenie w wodę; system odprowadzania ścieków; niskie dochody; sanitation condition; hygiene; low income community; water supply; latrine systems